Similarity in viral and host promoters couples viral reactivation with host cell migration - Kathrin Bohn-Wippert (Nature Portfolio, 2017)
The coevolution of viruses and host cells can be mapped with interactomics. Here the authors identify coupling of human and viral promoters, and show that HIV-reactivation from dormancy is coincident with migration of HIV-infected cells owing to coupling of human CXCR4 and HIV LTR promoters.